USULAN PENINGKATAN KUALITAS PADA PROSES PRODUKSI PT.KLM DENGAN PENDEKATAN LEAN SIX SIGMA DAN KAIZEN - Ines Rizkiyah (2021)
PT. KLM is a textile industry that is engaged in textile refinement. Based on historical data from PT. KLM in August 2019 - January 2020 total production was 347 000 with a defect number of 24290 or around 7%. Previously PT. KLM has a maximum defect percentage requirement of 5% for every single order. This study aims to identify waste in the form of defects, identify the causes of defects and design improvements in the warm tie dye production process in order to reduce the number of defects. Lean six sigma and kaizen methods were chosen to be implemented in overcoming existing defects. The result of this research is that the highest average of the questionnaire 7 waste is defect. The type of defect that has the highest is the motive that is not in accordance with the determined standard of 18265. Based on this research, it is known that the average sigma value is 3,794705779 which can be said that the company is at the 3σ level. PT.KLM needs to know the factors that cause defects in order to increase the sigma level. Based on the fishbone diagram, it can be seen that there are two factors that cause the defect type of motive not according to the standard, namely man and machine. PT. KLM can minimize defects by designing improvements that can be proposed by researchers, namely holding training for new operators on how to properly tie the cable ties, using a cable tie locking device, replacing existing cable ties with ISO standard cable ties and giving the operator a briefing before starting the engine.